Controle de constitucionalidade de leis penais e reserva de plenário - Azambuja Neto, Mario (2012)
In Brazilian courts, the statement - explicit or implicit - of unconstitutionality of the law or normative act of the public authorities cannot be performed by their fractional composition (chambers). It is assumed, as a condition of validity of the decision, the installation of an incident of unconstitutionality and consequent submission of the constitutional matters to the plenary or the special bench - if any - to the respective court (article 97 of the Federal Constitution and the binding precedent n. 10 of the Supreme Federal Court). This limitation on the jurisdiction action - supervened from the constitutional rule called "full bench system" - leads to the question about its scope: in which cases can the Courts' fractional benches quit from applyng the law without, in order to, have to submit themselves to the full bench system rule? In the criminal ambit the theme gains a variant even more exciting. This is becauses there are several theories and techniques tendeing to the removal of incriminating criminal law. The proper normative structure formed by the Federal Constitution and by the fundamental rights raises to the constitutional justice many possibilities for conforntation the legislation product, especially in the criminal area. The study proposes, therefore, some paths and definitions which would be the that require submission to the full bench system, with the specific staining of criminal science.